Leg and Joint Stiffness of the Supporting Leg during Side-Foot Kicking in Soccer Players with Chronic Ankle Instability - Akihiro Tamura; Keita Shimura; Yuri Inoue (MDPI AG, 2023)
Soccer players with chronic ankle instability (CAI) may stabilize their supporting leg by the proximal joint to compensate for the ankle instability during kicking motion. This study aimed to investigate the characteristics of leg and joint stiffness of the supporting leg during side-foot kicking in soccer players with CAI. Twenty-four male collegiate-level soccer players with and without CAI participated in this study. The kinematic and kinetic data were obtained using a three-dimensional motion analysis system. Leg stiffness and joint (hip, knee, and ankle) stiffness in the sagittal and frontal planes were calculated and analyzed. The results clarified that soccer players with CAI (0.106 ± 0.053 Nm/°) had greater knee stiffness in knee adduction during the kicking cycle compared to those without CAI (0.066 ± 0.030 Nm/°; p = 0.046), whereas no characteristic differences were observed in knee stiffness in knee flexion and hip and ankle stiffness (p > 0.05). Knee stiffness is believed to occur to compensate for ankle joint instability in the supporting leg. Therefore, adjusting knee stiffness to accommodate ankle joint instability is crucial for maintaining kicking performance. Based on results of this study, it may be important to consider training and exercises focused on joint coordination to improve knee stiffness in soccer players with CAI.